The relationship between postinjury symptomatology and days postinjury for the graded symptom scale in concussed adolescent athletes - Williams, R. M.; Bay, C.; McLeod, T. C. V. (International Journal of Athletic Therapy & Training, 2019)
Concussion symptoms are important self-reported indicators of recovery. The purpose of this study was to describe the symptom burden in the first 3 weeks postconcussion and estimate the strength of relationship between symptomatology and days postconcussion. Headache was the most commonly endorsed symptom during weeks 1 (71.1%), 2 (37.6%), and 3 (32.6%). Severity scores were negatively correlated with days postconcussion, p < .01. While headache is commonly reported following a concussion, and decreases with time, it was still endorsed 3 weeks postinjury. Clinicians should be aware that lingering symptoms may suggest a prolonged recovery that requires an active treatment approach.